137k views
2 votes
For the function f ( x ) = − 2x^2 + 2x + 8 , evaluate and fully simplify each of the following.

f ( x + h ) =

f ( x + h ) − f ( x ) =

1 Answer

6 votes

Answer:


f(x+h)=- 2x^2-4xh-2h^2 + 2x+2h + 8


f ( x + h ) - f ( x )= h(-4x-2h+2)

Explanation:

Given the function:


f ( x ) = - 2x^2 + 2x + 8

Find

  • f ( x + h )
  • f ( x + h ) - f ( x )

Recall the identity to square a binomial:


(a+b)^2=a^2+2ab+b^2


f(x+h)=- 2(x+h)^2 + 2(x+h) + 8

Squaring the binomial:


f(x+h)=- 2(x^2+2xh+h^2) + 2(x+h) + 8

Multiplying:


\boxed{f(x+h)=- 2x^2-4xh-2h^2 + 2x+2h + 8}

--------------------------------------------------------------

To compute f ( x + h ) - f ( x ), we use the last result:


f ( x + h ) - f ( x )=- 2x^2-4xh-2h^2 + 2x+2h + 8-(- 2x^2 + 2x + 8)

Multiplying:


f ( x + h ) - f ( x )=- 2x^2-4xh-2h^2 + 2x+2h + 8+ 2x^2 - 2x - 8

Simplifying similar terms:


f ( x + h ) - f ( x )= -4xh-2h^2+2h

Factoring:


\boxed{f ( x + h ) - f ( x )= h(-4x-2h+2)}

Note: This expression is commonly used to compute the first derivative of a function by its definition.

User Crayxt
by
5.9k points